Purity, sacrifice, and the temple: symbolism and supersessionism in the study of ancient Judaism - Klawans, Jonathan (Oxford University Press, 2006)
Sacrifice and purity -- The twisted fortunes of related ritual structures -- The sacrificial process of ancient Israel -- Rethinking the prophetic critique -- Temple as cosmos or temple in the cosmos -- Priests, purity, sacrifice, and angels -- Sinful people, impure priests, and inadequate structures -- The temple as defiled and rejected -- The purity of the Second Temple in Rabbinic literature -- The Last Supper, the temple incident, and the "spiritualization" of scarifice in the New Testament